PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GIVING QUESTION AND GETTING ANSWER (GQGA) UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR BIOLOGI SISWA KELAS VII.C MTS HASANAH PEKANBARU TAHUN AJARAN 2011/2012 - Mariani Natalina L; Rosmaini S; Nadya Yulia Novita (Program Studi Pendidikan Biologi, 2012)
There was applied the Class Action Research (CAR) in order to increase student’s scientific attitude and Biology study result of class VII.C in MTs Hasanah Pekanbaru by applying Cooperative Learning model GQGA. This research was conducted in May 2012. The measuring parameter in take focus on student’s scientific attitude that have 7 indicators and their study results that are the student’s intake, The student’s study accomplishment individually, team reward, and student’s and teacher activities. The rate of scientific attitude in cycle I is 61,92% (low) and increases in cycle II become 83,98% (good). Student’s capability in cycle I is 66,07 (standard) and increases to 72,53% (standard). The student’s study accomplishment can be seen from their daily evaluation test in cycle I is 75% (accomplished) and increases in cycle II become 89,28% (accomplished). The team reward in cycle I are 1 group in super team, and 4 in good team. In cycle II, 2 groups in super team, and 3 groups in good teams. The conclusion of this research can be taken that the cooperative learning mode of GQGA can increase the student’s scientific attitude and their Biology study result of class VII.C in MTs Hasanah Pekanbaru, Lesson Year 2011/2012Keywords: Biology Study Result, Giving Question And Getting Answer (GQGA), Scientific Attitude.